Infective Endocarditis caused by Enterococcus gallinarum - Dr Smriti Srivastava; Dr Priyanka Banerjee; Dr Drishti Sagar; Dr Manasvee Dewan; Dr Neha Sharma; Dr Mahendra Chouhan (International Journal of Infectious Diseases)
Introduction: Enterococcus gallinarum is a rare pathogen responsible for infective endocarditis (IE). This organism is resistant to multiple antimicrobials. Case Description: A 30-year-old man presented with a complaint of low-grade fever with intermittent spikes for 3 months; chest pain, shortness of breath and dry cough of two-week duration. He also reported associated malaise and anorexia for 3 months and weight loss of ∼ 9.5 kg over 3 months. On examination, he was febrile and had tachycardia. A pan systolic murmur was audible in the precordial area and radiated to the axilla. His Electrocardiogram showed sinus tachycardia and trans-thoracic echocardiography (TTE) exhibited severe mitral regurgitation and a bicuspid aortic valve with mild aortic regurgitation and mild aortic stenosis. Additionally, trans-esophagus echocardiogram (TOE) demonstrated a large echo density of anterior mitral leaflet measuring 1. ×  0.7 cm, consistent with vegetation, leading to the diagnosis of IE. Three separate blood cultures were obtained with the first and last samples collected 1 hour apart. Following overnight incubation at 37°C and subculture there was growth of gram-positive cocci, which were finally identified as E. gallinarum using conventional methods and VITEK 2 (BioMérieux, Marcy-l'Etoile, France), susceptible to linezolid, chloramphenicol, high-level gentamicin (synergy-testing) and teicoplanin. E. gallinarum is intrinsically resistant to quinupristin-dalfopristin (QD) and vancomycin.The treatment consisted of teicoplanin, in a loading dose of three 12-hourly 400 mg IV followed by a maintenance dose of 400 mg IV once daily in combination with gentamicin 80 mg IV q 12h. After 14 days of treatment, the mitral valve replacement was planned. The surgery went uneventfully, unfortunately, he succumbed to sudden cardiac death following a few months of discharge. Discussion: IE is caused by E.gallinarum in rare instances. Drug resistance inherent to enterococci leaves the physician with limited alternatives for treatment. For isolates resistant to vancomycin as well as beta-lactams, linezolid, QD, and daptomycin combinations can be given. With our patient, the isolate was resistant to penicillin and ampicillin, besides the intrinsic resistance to QD and vancomycin. However, high-level aminoglycoside resistance was absent. Hence, teicoplanin and gentamicin were given for 14 days in the standard dosage. There are reports of teicoplanin for the treatment of IE caused by VRE owing to adverse effects of other regimens. Our patient showed initial clinical improvement; however, the cause of the outcome could not be ascertained. Conclusion: IE caused by enterococci is difficult to treat and treatment needs to be tailored per the specific susceptibility results. Contemporary guidelines have not established the role of teicoplanin; however, few cases have been reported in the literature. More cases need to be studied to understand the optimum treatment of uncommon microbes of IE.